Efficient CdS quantum dot sensitized solar cells based on electrochemically reduced graphene oxide (ERGO)/ZnO nanowall photoanodes and MoS2, WS2, CuS cascaded counter electrodes. (1st March 2022) - Eryiğit, Mesut; Mobtakeri, Soheil; Gür, Eftade Pınar; Temur, Elif; Özer, Tuba Öznülüer; Demir, Ümit; Gür, Emre
Graphical abstract: Highlights: ERGO/ZnO nano-wall structures were synthesized succesfully in a one-step electrodeposition. CdS quantum dots 10–15 nm sizes were synthesized on ERGO/ZnO nano-wall photoanodes. WS2, MoS2 and CuS based counter electrodes were synthesized by sputtering and sulfurization. Successful quantum dot synthesized solar cells (QDSSCs) were produced with cascaded counter electrodes. The QDSSC with ERGO/ZnO/CdS composite exhibit a high efficiency of 2.74%. Abstract: The electrochemical reduction of graphene oxide (ERGO) and electrochemical formation of ZnO were carried out simultaneously on transparent conductive substrates by one-pot technique at the same potential. Vertically aligned and homogeneously distributed ZnO nanowall structures on electrochemically reduced graphene oxide (ERGO) were decorated with semiconductor CdS quantum dots (QDs) by using a successive ionic layer adsorption and reaction (SILAR) method. Electrochemically grown hierarchical ERGO/ZnONWs/CdS photoanodes showed better light-harvesting efficiency and higher photo-generated electron concentration compared to ERGO/ZnO NWs and bare ZnO electrodes. Counter electrodes (CE) with single layer, double cascaded and triple cascaded hetero-structures of MoS2, WS2 and Cux S were synthesized by two step method with RF-magnetron sputtering and thermal sulfurization methods The performance measurements of QDSSCs fabricated with Cux S CEs with variable stoichiometric composition (x = 1, 1.8, 2) have displayed that quantum dot sensitized solar cells (QDSSCs) with Cu-deficient CEs have better device performances, which is lower compared to the QDSSC with of MoS2 and WS2 CEs. As the combination of CEs are considered, the best device performance has been achieved with MoS2 /WS2 /CuS CE which is 2.74% power conversion efficiency with 45% peak quantum efficiency. Cascaded CE structures along with the ERGO/ZnONWs/CdS photoanode have been suggested as good candidate for QDSSCs.